Epidemiological trends and projections to 2035 of hepatitis B burden in China, 1990–2021 - Xinyue Qi; Yongzheng Hu; Wei Jiang (PLoS ONE, 2025)
Background Hepatitis B virus (HBV) remains a major cause of liver disease and premature death globally, with China bearing a significant share of the burden. However, long-term trends and future projections of HBV burden in China remain insufficiently described, despite widespread infant vaccination and expanded antiviral therapy. Methods We analyzed hepatitis B–related mortality, age-standardized mortality rate (ASMR), disability-adjusted life years (DALYs), and age-standardized DALY rate (ASDR) in China from 1990 to 2021 using data extracted from the GBD 2021 database. Temporal trends were quantified by estimated annual percentage change (EAPC). Results Between 1990 and 2021, the number of deaths from hepatitis B-related liver diseases in China increased from 215 thousand to 219 thousand (+1.83%), whereas the ASMR decreased from 23.86 per 100,000 to 10.68 (EAPC: −2.78). The disability-adjusted life years (DALYs) decreased from 7.78 million in 1990 to 6.61 million in 2021 (−15.04%), with the ASDR decreasing from 774 per 100,000–329 (EAPC: −3). Despite significant reductions in HBV mortality and DALYs, the growing burden of HBV-related liver cancer, particularly among older males, remains a critical concern. Targeted early screening and treatment strategies are urgently needed. Projections for 2035 indicate a continued decline in the overall burden of hepatitis B, with the liver cancer burden showing a fluctuating decrease. Conclusion Despite progress in HBV prevention and control, the increasing burden of hepatitis B–related liver cancer remains a major public health challenge.